A temperature-sensitive metabolic valve and a transcriptional feedback loop drive rapid homeoviscous adaptation in Escherichia coli - Hoogerland, Loles; van den Berg, Stefan Pieter Hendrik; Suo, Yixing; Moriuchi, Yuta W.; Zoumaro-Djayoon, Adja; Geurken, Esther; Yang, Flora; Bruggeman, Frank; Burkart, Michael D.; Bokinsky, Gregory (Nature communications, 2024)
All free-living microorganisms homeostatically maintain the fluidity of their membranes by adapting lipid composition to environmental temperatures. Here, we quantify enzymes and metabolic intermediates of the Escherichia coli fatty acid and phospholipid synthesis pathways, to describe how this organism measures temperature and restores optimal membrane fluidity within a single generation after a temperature shock. A first element of this regulatory system is a temperature-sensitive metabolic valve that allocates flux between the saturated and unsaturated fatty acid synthesis pathways via the branchpoint enzymes FabI and FabB. A second element is a transcription-based negative feedback loop that counteracts the temperature-sensitive valve. The combination of these elements accelerates membrane adaptation by causing a transient overshoot in the synthesis of saturated or unsaturated fatty acids following temperature shocks. This strategy is comparable to increasing the temperature of a water bath by adding water that is excessively hot rather than adding water at the desired temperature. These properties are captured in a mathematical model, which we use to show how hard-wired parameters calibrate the system to generate membrane compositions that maintain constant fluidity across temperatures. We hypothesize that core features of the E. coli system will prove to be ubiquitous features of homeoviscous adaptation systems. Free-living microorganisms regulate the fluidity of their membranes by adapting lipid composition to environmental temperatures. Here, the authors quantify lipid biosynthetic enzymes and metabolic intermediates to provide a quantitative description of how the bacterium Escherichia coli maintains constant membrane fluidity after a temperature shock.